INFLUENCE ONLINE GAME POINT BLANK FOR LANGUAGE SKILLS POLITE INCOMMUNICATING BETWEEN PEER STUDENT - Aj Dara; Adelina Hasyim; Hermi Yanzi (Jurnal Kultur Demokrasi, 2012)
The purpose of this study was to determine the effect of Point Blank Games Online Courtesy Of Language Skills In Communication Between Students of SMP YP 17 Baradatu Kab. Way Kanan in 2012.The method used in this research is descriptive method, and using the basic techniques of data collection using questionnaires. In this study there were 25 respondents. And techniques of data analysis using interval and chi squared formula. Based on the results of this research, the influence of Online Game Point Blank on student explains that when they playing Online Game Point Blank they often used a languages are not polite to fellow friends, students are enjoying and feel satisfied when using bad language which is not polite to use between peers of students when Point Blank Online Game play. Based on the above explanation shows that the influence of Point Blank Online Game play is very close to the habits of polite language in communicating among fellow friends.Key Word: influence online game, language skills politc,skills communicating